Apnoeic oxygenation in paediatric anaesthesia: a narrative review. (27th June 2020) - Lyons, C.; Callaghan, M.
Summary: Apnoeic oxygenation refers to oxygenation in the absence of any patient or ventilator effort to move the lungs. This phenomenon was first described in humans in the mid‐20th century but has seen renewed interest in the last decade following the demonstration of apnoeic oxygenation with low‐flow, and subsequently high‐flow, nasal oxygen. This narrative review summarises our understanding of apnoeic oxygenation in the paediatric population. We examine the evidence supporting oxygenation via tracheal tube, modified laryngoscopes and nasal cannulae. The evidence for prolongation of safe apnoea time at induction of anaesthesia is also appraised. We explore the capacity for carbon dioxide clearance, flow rate selection with high‐flow nasal oxygen and complications associated with the technique. It remains uncertain whether apnoeic oxygenation in paediatric patients results in a meaningful clinical benefit compared with standard care for outcomes such as the number of tracheal intubation attempts or the incidence of hypoxaemia. In particular, the role of apnoeic oxygenation in paediatric difficult airway management is unclear as this has not been the targeted focus of any published research to date.